2016
DOI: 10.1097/mpg.0000000000001288
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for An Algorithm for Screening for Undernutrition in Hospitalized Children

Abstract: The prevalence of disease-related undernutrition in hospitalized children has not decreased significantly in the last decades in Europe. A recent large multicentric European study reported a percentage of underweight children ranging across countries from 4.0% to 9.3%. Nutritional screening has been put forward as a strategy to detect and prevent undernutrition in hospitalized children. It allows timely implementation of adequate nutritional support and prevents further nutritional deterioration of hospitalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Recent studies reported that disease-related malnutrition (DAM), which can be defined as malnutrition in the context of acute and/or chronic disease, is highly prevalent in hospitalized children in North America [ 1 , 2 , 3 ]. Nine percent of the children had a body mass index (BMI) or weight for height (WFH) below −2 SD on admission [ 1 , 2 ], which is in close agreement with figures reported in Europe [ 4 ]. The use of WFH < −2 SD or BMI < −2 SD (or WFA < −2 SD for infants) as indicators of malnutrition stems from recommendations made by the World Health Organization to screen for children with malnutrition.…”
Section: Introductionsupporting
confidence: 82%
“…Recent studies reported that disease-related malnutrition (DAM), which can be defined as malnutrition in the context of acute and/or chronic disease, is highly prevalent in hospitalized children in North America [ 1 , 2 , 3 ]. Nine percent of the children had a body mass index (BMI) or weight for height (WFH) below −2 SD on admission [ 1 , 2 ], which is in close agreement with figures reported in Europe [ 4 ]. The use of WFH < −2 SD or BMI < −2 SD (or WFA < −2 SD for infants) as indicators of malnutrition stems from recommendations made by the World Health Organization to screen for children with malnutrition.…”
Section: Introductionsupporting
confidence: 82%
“…Nutritional screening is considered a key part of the hospital nutrition care process and pediatric nutritional care algorithm [37]. A number of recent studies have focused on the organizational aspect of nutritional screening, focusing on auditing local or national practices [38,39 & ,40], describing barriers hindering optimal nutrition care [39 & ,40,41], and propositions to simplify or improve current practices [38,39 & ,42].…”
Section: Screening and Hospital Nutrition Care Processmentioning
confidence: 99%
“…Independently of the income setting, malnutrition is multifactorial. Whereas malnutrition in low-income countries is often, but not solely, attributable to limited access to food and/or medical care, it is often triggered by disease in in-transition countries [5,6]. Of importance, the report of the Global Burden of Disease Study 2013 revealed that protein-energy malnutrition accounted globally for 9.8/100.000 age-standardized deaths in the largest 50 countries for child and adolescent populations.…”
Section: Introductionmentioning
confidence: 99%